Labor Economics - Kamilova, Amina (ADA University, 2018)
As time passes and the world population accrues a greater amount, this gradual growth engenders the discussions about the issues concerning to the social and financial domains more. One of the cardinal and arduous parts of these issues can be contented as the decision-making process of the job enrollment or specialization, workplace choice, salary earnings, consumption and leisure allocations, and so on. “The most important social welfare program in America is a job”. The former Speaker of the United States House of Representatives, Newt Gingrich expressed the significance of the job with this quote. As the job market is in the interest of many people there are many discussions and researches devoted to this issue and more professionally labor economics is considered as an apropos tool, which delineates various demotic problems and their effects in the job sector, and apprises the community about the possible solutions to them. Due to the reason that labor economics alludes to employment as a critical part of social and governmental issues, to my point of view, it is worth to conduct a study relating to it. The labor market described as consisting of three significant actors, who are employees, employers, and government. Government interventions are inevitable and intense part of controlling labor market. In addition to government interference, there also exist private organizations, which sustain the employers in ameliorating their working conditions, salaries by creating so-called labor unions. And wage is the payment to the employees by private enterprises or governmental institutions. The goal of this paper is to conduct a research about the effects of annual wages and labor unions on the employment level. Although there are numerous of works related to that topic there is a need for the study that unifies the variables that I combined in this paper for more specific and precise estimations. For this research, Netherlands is chosen as the target location, which is in the list of countries where I can live in future. Coming to question why especially this concept, there are several reasons. First of all, in Chapter 3 we have covered the consequences of wage reduction that explained by marginal cost approach, and substitution and scale effect approach and both characterizing the effect as the rise in employment. Secondly, in Chapter 12 we have covered the types of unemployment and in this section the structural unemployment and one of its reasons-labor unions got my attention. Thus, as in the contemporary society both private sector (labor unions, wages) and governments (wages) espouse into the employment levels by taking initiatives in order to bolster the economy and community, I wanted to conduct an empirical study relating to the above-mentioned two theories and explore whether they apply in reality in Netherlands or not. Considering the three discrete interesting topics, deriving an expository investigation of their relationship would amalgamate allure and efficacy in it. There is of course, some work that examines this relationship; nevertheless, my work focuses on the effects of collective bargaining percentage that describes a labor union power and existence, and annual wages together with the intermediate educational population percentage of labor force and GDP effects on employment level that as far as I researched not have been in the same regression model. Regarding to the raise of hypothesizes of labor unions a paper by Villanueva Ernesto, where he concludes the collective bargaining benefit as reduction in wage inequality and cost as causing less employment (2015, p.3-4). On the other hand, another detailed paper stated that exploring the 1970s and the 1980s, Bruno and Sachs (1985) found a positive relationship of collective bargaining and lower unemployment (Adascalitei, Dragos, Khatiwada,Miguel A.,Pignatti Morano, 2015, p.8). Furthermore, in one of the papers it is argued that wage decline is successful initiative to consider to increase employment and output level due to the marginal cost reduction ( R.B.Bangs, 1942, p.256). Additionally, an article by Ryan Fuhrman stated that the economic growth measured by GDP causes a fall in the unemployment rate (2008). Finally, another paper mentioned that educational decision is important, as the unemployment rate is lower for the skilled proportion of the people (Brauninger.M, 2000, p.499). All of these sources provide us with the useful information about the interactions among the variables; however, there is a need to run regression in order to have specific outcomes.
Keywords: Labor economics.; Industrial relations.; Working class